Decision-Making Regarding Ventilator Support in Children with SMA Type 1—A Cross-Sectional Survey among Physicians - Pechmann, Astrid; Langer, Thorsten; Kirschner, Janbernd (Neuropediatrics, 2019)
Spinal muscular atrophy (SMA) is a neuromuscular disorder characterized by muscle atrophy and severe proximal muscle weakness. In the absence of curative treatment, it has been controversial whether critically ill infants with SMA type 1 should receive ventilator support. The aim of this study was to investigate the process of decision-making regarding ventilator support in children with SMA type 1 from the perspectives of physicians. A web-based survey with 17 questions and 2 case vignettes was conducted in 671 physicians in Germany and Switzerland from 12/2016 to 03/2017. The survey focused on factors influencing the decision about ventilator support and the content in informed consent discussions. Additionally, physicians were asked about their general attitude towards mechanical ventilation in children with SMA type 1 and their hypothetical clinical management in emergency settings using case vignettes. Hundred and sixty-five physicians participated in the survey (50.3% child neurologists, 18.8% specialists for ventilator support, 6.1% pediatric palliative care physicians, and 6.1% with more than one of these specializations). Of all physicians, 44.2% confirmed to have experience with SMA type 1 patients using ventilator support. In summary, our results show that physicians' attitudes and experiences about mechanical ventilation in children with SMA type 1 vary considerably and are likely to influence the outcome in informed consent discussions and the hypothetical management in emergency settings.
Keywords: spinal muscular atrophy; SMA; ventilator support; decision-making